2019
DOI: 10.1017/s0007114519000047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pyrroloquinoline quinone disodium in female rats during gestating and lactating on reproductive performance and the intestinal barrier functions in the progeny

Abstract: The objective of this study was to investigate the effects of dietary pyrroloquinoline quinone disodium (PQQ·Na2) supplementation on the reproductive performance and intestinal barrier functions of gestating and lactating female Sprague–Dawley (SD) rats and their offspring. Dietary supplementation with PQQ·Na2 increased the number of implanted embryos per litter during gestation and lactation at GD 20 and increased the number of viable fetuses per litter, and the weight of uterine horns with fetuses increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
2
9
0
Order By: Relevance
“…In this study, the mRNA expression of Occludin and ZO-1 were increased in the jejunal of weaned piglets with the PQQ•Na 2 supplementation. Zhang et al [17] reported that dietary PQQ•Na 2 supplementation during gestation and lactation of female rats can significantly increase the expression of ZO-1 and Claudin mRNA in the jejunal mucosa of weaned rats which is consistent with our study results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the mRNA expression of Occludin and ZO-1 were increased in the jejunal of weaned piglets with the PQQ•Na 2 supplementation. Zhang et al [17] reported that dietary PQQ•Na 2 supplementation during gestation and lactation of female rats can significantly increase the expression of ZO-1 and Claudin mRNA in the jejunal mucosa of weaned rats which is consistent with our study results.…”
Section: Discussionsupporting
confidence: 92%
“…The weaning process for pigs involves an abrupt dietary shift from sow milk to a completely feed-based diet that produces abrupt taxonomic and functional shifts in the intestinal microbiota [16]. PQQ•Na 2 has been reported to have an impact on the intestinal microbiota [17]. However, the impact of maternal dietary PQQ•Na 2 supplementation on the intestinal microbiota in offspring is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the mRNA expression of Occludin and ZO-1 were increased in the jejunal of weaned piglets with the PQQ•Na 2 supplementation. Zhang et al [17] reported that dietary PQQ•Na 2 supplementation during gestation and lactation of female rats can signi cantly increase the expression of ZO-1 and Claudin mRNA in the jejunal mucosa of weaned rats which is consistent with our study results.…”
Section: Discussionsupporting
confidence: 92%
“…Dietary supplementation with PQQ has been shown to improve neonatal growth and decrease redox potential in animals ( Killgore et al, 1989 ; Wang et al, 2015 ). The weaned pups of female rats that were administered PQQ-supplemented diets during gestation and lactation could increase intestinal tight junctions proteins expression ( Zhang et al, 2019 ). Furthermore, PQQ has been shown to regulate levels of jejunal inflammatory factors in weaned piglets ( Zhang et al, 2020 ) and promote T-cell immunological memory during immune responses ( Rucker et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%